Meu Caro Eudaldo: edição dos rascunhos de cartas do caderno farmácia São José, de Eulálio Motta - Santiago, Stephanne da Cruz (2021)
Meu caro Eudaldo: edição dos rascunhos de cartas do caderno Farmácia São José, de Eulálio Motta is a work based on the personal holdings of Eulálio de Miranda Motta, writer from Mundo Novo–BA, who kept, among other varied documents, 15 handwritten notebooks. Among them, the Farmácia São José draftbook, that has 132 texts presenting different subject-matters, predominantly religious, which 53 of them are drafts of letters. Nineteen of these drafts were written to be sent to a Motta’s childhood friend named Eudaldo Silva Lima, were written between 1941 and 1942, and served as a stage for a religious debate about Catholicism and Protestantism that transcended the private sphere. Taking this corpus as base, it was discussed, using texts of Scholarly Edition from Brazil (CAMBRAIA, 2005; BORGES e SOUZA, 2012; BARREIROS, 2015), Portugal (DUARTE, [1997-]), USA (WILLIAMS and ABBOTT, 1999; SHILLINGSBURG, 2004) and France (CERQUIGLINI, 2000), and also texts of Genetic Criticism from Brazil (PINO and ZULAR, 2007) and France (HAY, 2007; BIASI, 2010) some issues involving the editing and transcription of documents that present marks of the writing process, such as erasures and amendments. To support theoretically the edition, it was also used the discussions of McKenzie (2005) and Moreira (2012), which deal with the importance of exploring beyond the linguistic code of the documents in order to meet the contextual and material needs of a document in an edition. It is also presented a general contextualization of the epistolary kept in the holdings of Eulálio Motta, reaveling his production of drafs of letters in his work notebooks, his addressees and the different uses of the genre, correlating with the production of drafts of letters in the Farmácia São José draftbook. Furthermore, a documentary edition with the material description is presented (MILEVSKI, 2001; PAGLIONE, 2017), the internal structuring of the notebook, the contextualization of Motta’s religious profile and the thematic description of the edited corpus, as well as the genetic transcriptions and their preparation for processing in the AntConc software, due to linguistic study, based on the discussions of the Corpus Linguistics and the preparation of corpora for lexical studies (BERBER SARDINHA, 2004; OTHERO, 2016; BARREIROS, L., 2017). This work shows relevance for dealing with editions of documents with marks of writing process, presenting an edition of documents that reveal a religious discussion about Catholicism and Protestantism between a writer from the interior of Bahia and a Presbyterian pastor, also born in Mundo Novo–BA, for editing documentation that can provide studies about the Bahian modernist scenario and for preparing corpora for the lexical study using the AntConc software. All these elements that this work aimed to contemplate are in the interest of the projects Edição das Obras Inéditas de Eulálio Motta and Estudos lexicais no Acervo de Eulálio Motta.